Grammatical Cohesive Devices of Students Writing Recount Text in Vocational High School - Wiyanto, Muhammad Saibani; Brilianty, Annisa (Universitas Muhammadiyah Mataram, 2025)
This study aims to identify the types and the meaning of grammatical cohesive devices in students’ recount texts. The object of the study was 26 recount texts written by tenth-grade students. Data were collected through documentation and analyzed using qualitative content analysis as proposed by Mayring (2014), involving categorization, abstraction, and coding based on Halliday and Hasan’s cohesion framework. The analysis revealed 590 instances of grammatical cohesive devices. Reference was the most frequently used, occurring 460 times, indicating students’ strong dependence on personal and demonstrative references to maintain coherence. Conjunctions were the second most common, with 129 instances, demonstrating their role in connecting events and ideas. Substitution appeared only once, while ellipsis was not found in any of the texts. The study concludes that reference and conjunction are the dominant cohesive devices used by students in constructing recount texts, helping to maintain the logical flow and coherence of their narratives. The rare use of substitution and the absence of ellipsis suggest these forms are less familiar to students and require further instructional emphasis. This analysis highlights the importance of grammatical cohesion in supporting the clarity and unity of student writing.